2013
DOI: 10.1093/europace/eut145
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent effect of cardiac resynchronization therapy on ventricular repolarization and ventricular arrhythmias

Abstract: Transmural dispersion of repolarization and the number of patients with VT/VF decreased over time after CRT. Patients with reverse remodelling demonstrated a lower rate of VT/VF and a greater time-dependent reduction of TDR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 27 publications
2
30
0
Order By: Relevance
“…However, CRT totally changes left ventriclular direction of depolarization and repolarization since its epicardial pacing, leading to TDR increasing36. It was reported that occurrence of tachycardia was higher in early stage of CRT implantation37. In this study, compared to baseline, TpTe and QT which reflect the degree of TDR were significantly increased within 72 h after CRT implantation (100 ± 20 ms vs. 119 ± 24 ms, and 446 ± 58 ms vs. 455 ± 56 ms respectively, p < 0.01, indicating that CRT increases the dispersion of repolarization and has potential to cause arrhythmia in the early stage (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, CRT totally changes left ventriclular direction of depolarization and repolarization since its epicardial pacing, leading to TDR increasing36. It was reported that occurrence of tachycardia was higher in early stage of CRT implantation37. In this study, compared to baseline, TpTe and QT which reflect the degree of TDR were significantly increased within 72 h after CRT implantation (100 ± 20 ms vs. 119 ± 24 ms, and 446 ± 58 ms vs. 455 ± 56 ms respectively, p < 0.01, indicating that CRT increases the dispersion of repolarization and has potential to cause arrhythmia in the early stage (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Reverse electrical remodeling: The present study demonstrates that CRT reduces paced QRS duration as well as TDR at 1‐year postimplantation. The magnitude of reduction in TDR is significantly greater in high responders compared with low responders, as demonstrated previously . The mechanism of reverse electrical remodeling due to CRT has not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Itoh et al. demonstrated time‐dependent reduction in ventricular arrhythmias in patients with CRT, with greater reductions in CRT responders as opposed to nonresponders . They also observed that Tp‐e 1 week after CRT implantation was significantly higher compared to baseline.…”
Section: Discussionmentioning
confidence: 99%
“…17 Episodes of VT and/or VF detected by the implanted device were validated by two electrophysiologists. 18,19 Electrocardiography (ECG) All patients received two intrinsic ECGs, one was performed before the CRT and the other was performed after transient turn-off of CRT for about 30 minutes before. Intrinsic QRS duration (iQRSd) was measured from the initial to the end of QRS wave.…”
Section: Patient Populationmentioning
confidence: 99%